Oxypoda demissa Casey 1911 - Webster, Reginald; Klimaszewski, Jan; Pelletier, Georges; Savard, Karine (Zenodo, 2009)
Oxypoda demissa Casey, 1911 Fig 17, Map 17 New Records. CANADA, New Brunswick, Carleton Co. , near “ Two Mile Brook Fen ”, 46.3510°N, 67.6815°W, 6.V.2005, M.-A. Giguère and R.P. Webster (1 ♁, RWC); near Hovey Hill Protected Area, 46.1152°N, 67.7632°W, 10.V.2005 (1 ♀, RWC). Restigouche Co. , Jacquet River Gorge PNA, 47.7357°N, 67.0774°W, 24.VI.2008 (1 ♀, RWC). York Co. Charters Settlement, 45.8428°N, 66.7279°W, 20.IV.2005 (1 ♁, 1 ♀, RWC); Charters Settlement, 45.8395°N, 66.7391°W, 23.IV.2008 (2 ♁, 2 ♀, Map Į7. Collection localities in New Brunswick, Canada of Oxypoda demissa . RWC); 8.0 km NW of Magundy, 45.8712°N, 67.2221°W, 8.VII.2006 (1 ♀, RWC); 8.4 km W of Tracy off Rt. 645, 45.6821°N, 66.7894°W, 14.V.2008 (1 ♀, RWC). Bionomic Notes. Oxypoda demissa appears to be a hygrophilous species associated with wet habitats of various kinds. In New Brunswick, adults were captured in moist leaf litter on the margin of a vernal pond in a mixed forest, among leaves and sedges on pond margin, in moist grass litter and sphagnum in Carex marsh, among sedges along margin of small spring-fed brook in a mature hardwood forest and among leaf litter and grass on hummocks in a wet alder ( Alnus sp.) swamp. In Nova Scotia, this species was reported from litter of Alnus clumps (Klimaszewski et al. 2006). A number of adults were collected with a net during late afternoon (15:00 to 18:00 h) flights. Adults were captured in April, May, June, and July. Collection method: sifting, some collected in flight with net during evening. Distribution in Canada and Alaska. YT, ON, QC, NB , NS, NF & LB (Klimaszewski et al. 2006; Gouix and Klimaszewski 2007; Klimaszewski et al. 2008b). : Published as part of Webster, Reginald, Klimaszewski, Jan, Pelletier, Georges & Savard, Karine, 2009, New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae, pp. 171-248 in ZooKeys 22 (22) on pages 193-194, DOI: 10.3897/zookeys.22.152, http://zenodo.org/record/576537 : {"references": ["Casey TL (1911) New American species of Aleocharinae and Myllaeninae. Memoirs on the Coleoptera 2. Th e New Era Printing Co., Lancaster, Pennsylvania.", "Gouix N, Klimaszewski J (2007) Catalogue of Aleocharine Rove Beetles of Canada and Alaska (Coleoptera, Staphylinidae, Aleocharinae). Pensoft Publishers, Sofia-Moscow, 165 pp.", "Klimaszewski J, Savard K, Pelletier G, Webster R (2008 b) Species review of the genus Gnypeta Thomson from Canada, Alaska and Greenland (Coleoptera, Staphylinidae, Aleocharinae): systematics, bionomics and distribution. ZooKeys 2: 11 - 84."]}